Influence of Aerobic Training and Selected Asanas Modulates Serum Lipds and Lipoproteins in Young Obese Males - Suthakar Krishnaswamy1, Annida Balakrishnan3, P. Anandhan 1,2*, K.V. Balamurugan1 (Journal of Experimental Sciences, 2010)
Abstract The aim of the study was to analyze the effect of aerobic training and selected asanas on serum lipids and lipoproteins in young obese men. To achieve the purpose, sixty obese male students were selected randomly from different faculties of Annamalai University, and their age ranges between 18 to 25 years. Selected subjects were classified into three groups with twenty members of each. Group 1 served as control, Group 2 act as aerobic training and Group 3 as asanas training group. Exercise training such as aerobic exercise and selected asanas were given to the experimental training groups for a period of three months (4 days/ week) whereas the control group was given no special training other than regular activities. Blood samples were collected before and after the completion of full training course. Biochemical analyses were done on serum lipids (total cholesterol, triglycerides, free fatty acids and total phospholipids) and plasma lipoproteins (VLDL, LDL and HDL) to find out the significant effect of training on obese men. The data were collected and statistically analyzed using ANOVA and DMRT and they are significant at p<0.01. The resulted study shows significant changes in the serum lipids and lipoprotein levels in the experimental training groups than control; The study shows that both the training groups produced their effect in modifying the serum lipids and lipoproteins thereby retains the HDL level. It was also revealed that much better effect was seen only in aerobic training group. Keywords: Obesity, Aerobic training, Asanas, Serum lipids, Plasma lipoproteins --- 1Department of Physical Education and Sports Science, Annamalai University, Chidambaram – 608 002. Tamil Nadu, India ; 2No: 10, Tamil Marai Street, Vandi Medu, Villupuram – 605 602, Tamil Nadu. (India); 3Department of Biochemistry, Sathyabama University Dental College and Hospital, Chennai -117.Tamil Nadu, India --- Please Cite This Article As: P. Anandhan, K.V. Balamurugan, Suthakar Krishnaswamy, Annida Balakrishnan. 2010. Influence of Aerobic Training and Selected Asanas Modulates Serum Lipds and Lipoproteins in Young Obese Males. J. Exp. Sci. 1(6):17-20.